Analysis Of Financial Statement Preparation According To Isak 35 At SMK Swasta Bina Guna Tanah Jawa Simalungun - Dedy Damhuri; Arnida Wahyuni; Nurwani Nurwani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The purpose of this research is to determine the preparation of financial reports according to ISAK 35 at the Tanah Java Private Bina Guna Vocational School. This research uses descriptive qualitative methods. Data collection techniques were obtained through observation, interviews and documentation. The data obtained are primary data and secondary data. The results of this research indicate that the financial reports of the Bina Guna Tanah Jawa Private Vocational School are not in accordance with ISAK 35. The obstacles faced by the treasurer's lack of understanding and skills in preparing financial reports in accordance with ISAK 35. For this reason, the School Treasurer must immediately prepare financial reports in accordance with the Interpretation of Accounting Standards Finance 35 which is currently in effect is in the form of preparing a report of financial position, comprehensive income report, report on changes in net assets, cash flow report, and notes to financial reports.Keywords: Financial Statements, ISAK 35, Non-Profit Entity